2012
DOI: 10.1094/mpmi-09-11-0252
|View full text |Cite
|
Sign up to set email alerts
|

Cucumis melo MicroRNA Expression Profile During Aphid Herbivory in a Resistant and Susceptible Interaction

Abstract: Aphis gossypii resistance in melon (Cucumis melo) is due to the presence of a single dominant virus aphid transmission (Vat) gene belonging to the nucleotide-binding site leucine-rich repeat family of resistance genes. Significant transcriptional reprogramming occurs in Vat(+) plants during aphid infestation as metabolism shifts to respond to this biotic stress. MicroRNAs (miRNAs) are involved in the regulation of many biotic stress responses. The role of miRNAs was investigated in response to aphid herbivory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 44 publications
3
46
0
Order By: Relevance
“…All of these plant miRNAs were also present in melon sRNA libraries [23], [24]. Two of the six, miR166 and miR168, were identified in the Vat + aphid library.…”
Section: Resultsmentioning
confidence: 96%
“…All of these plant miRNAs were also present in melon sRNA libraries [23], [24]. Two of the six, miR166 and miR168, were identified in the Vat + aphid library.…”
Section: Resultsmentioning
confidence: 96%
“…In the first batch, 23 nt sRNAs were the most abundant in 10DAF and 20DAF libraries, and 24nt for 30DAF and 40DAF libraries; while in the second batch, 24 nt was the major size of sRNAs in 10DAF and 20DAF libraries, and 21 nt was the major size in 30DAF and 40DAF libraries. Endogenous sRNAs of 24 nt are the most abundant sRNAs in some fruit crops, such as cucumber [36], apple [21], sweet orange [25], pear [26] and aphid susceptible and resistant melon breeding lines [37]. In contrast, 21 nt is the predominant size of sRNAs identified from RNA viruses susceptible and resistant melon cultivars [20].…”
Section: Resultsmentioning
confidence: 99%
“…Defense pathways and related phytohormone-mediated responses are strongly induced in response to hemipteran feeding (Moran and Thompson, 2001; Smith and Boyko, 2007; Morkunas et al, 2011). During the last decade, studies have revealed that sRNAs serve as important modulators of plant stress responses in response to phloem-feeding insects (Greyling, 2012; Sattar et al, 2012b; Barah et al, 2013; Kettles et al, 2013; Xia et al, 2015) (Table 1). Important milestones in our understanding of sRNA function in basal immunity against hemipteran insects have been made in Arabidopsis; however, parallel investigations in non-model systems are revealing the role of sRNAs in host plant resistance.…”
Section: Host Srna Pathway Components and Induced Responses Against Hmentioning
confidence: 99%
“…Resistance to cotton-melon aphids is exhibited as antixenosis (non-preference), antibiosis (delayed growth and development and reduced reproduction), and host plant tolerance (Bohn et al, 1972). The melon miRNA expression profile was determined using sRNAseq combined with comparative analysis of miRNA expression patterns in response to aphid herbivory during resistant and susceptible interactions (Sattar et al, 2012b). Libraries generated from leaf tissues of Vat + aphid-resistant melon plants with and without aphids compared the sRNA expression at initial stages of the interaction to distinguish between the molecular cues that are associated with early (2, 4, and 6 h) and late (8, 10, and 12 h) stages that corresponded with pre- and post-sustained phloem ingestion, respectively (Klingler et al, 2001).…”
Section: Host Srna Pathway Components and Induced Responses Against Hmentioning
confidence: 99%
See 1 more Smart Citation